Adaptive Mesh Refinement MHD Simulations of Tokamak Refueling - Samtaney, Ravi (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Introduction Mathematical Models, Equations, and Numerical Method Simulation Results Summary and Future Work Acknowledgments References